2016
DOI: 10.3109/0284186x.2016.1142115
|View full text |Cite
|
Sign up to set email alerts
|

Deep inspiration breath-hold volumetric modulated arc radiotherapy decreases dose to mediastinal structures in locally advanced lung cancer

Abstract: The phase III dose escalation trial RTOG 0617 [4] showed that heart dose parameters were correlated to death in a multivariate analysis and in a dose escalation trial by Cannon et al.[5] serious late toxicity from central and perihilar structures was encountered. In breast cancer radiotherapy a large population-based case-control study showed an increased risk of major cardiac events with increasing heart dose [6]. During deep inspiration breath-hold (DIBH), the lungs are inflated and the heart displaced cauda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Of note, most studies in lung cancer investigate the link between outcomes and planned dose (as opposed to delivered dose). However, the set-up uncertainties and anatomical motion impacts the dose received by the heart and heart sub-structures, and thereby the risk of RIHD ( 44 ).…”
Section: Real-world Data In the Context Of Radiation Induced Heart Di...mentioning
confidence: 99%
“…Of note, most studies in lung cancer investigate the link between outcomes and planned dose (as opposed to delivered dose). However, the set-up uncertainties and anatomical motion impacts the dose received by the heart and heart sub-structures, and thereby the risk of RIHD ( 44 ).…”
Section: Real-world Data In the Context Of Radiation Induced Heart Di...mentioning
confidence: 99%
“…Deep inspiration breath-hold (DIBH) is an active respiratory motion management strategy that involves the delivery of radiotherapy during breath-hold. It results in increased lung volume and displacement of the heart and can therefore be used to reduce normal tissue dose [25,26]. Respiratory gating is another active respiratory motion management strategy.…”
Section: Passive Versus Active Respiratory Motion Managementmentioning
confidence: 99%
“…In the deep-inspiration breath-hold (DIBH), the patient attempted a maximum inhalation during simulation and treatment, by using spirometer linked to a video glasses or a screen (20). This technique allows the displacement of heart and lung from the high-dose region (21,22). Rosenzweig et al (23) showed that normal tissue complication in lung decreased with the DIBH technique compared with freebreathing.…”
Section: Breath-hold Techniquesmentioning
confidence: 99%